Necrotizing Fasciitis Secondary to Blunt Trauma - Ömer Arda Çetinkaya; Süleyman Utku Çelik; Hakan Uncu (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Necrotizing fasciitis is a rare, rapidly progressive, and potentially fatal soft tissue infection of the skin, subcutaneous tissue, fascia, or muscles. Only early clinical suspicion, appropriate an-timicrobials, rapid and aggressive surgical debridement can reduce mortality and morbidity. Even with effective treatment and all care interventions, necrotizing fasciitis is a disease that is difficult to manage. In this report, we present a necrotizing fasciitis case of a 48-year-old male with blunt gluteal trauma after falling on stairs.